Effect of Periodic Fluctuations of Cutting Mode Parameters on the Temperature of the Front Face of a Turning Tool - E. V. Fominov; V. E. Gvindjiliya; A. A. Marchenko; C. G. Shuchev (Advanced Engineering Research, 2025)
Introduction. Modern research aimed at improving the efficiency of the workpart procedures emphasizes the importance of taking into account the effect of periodic disturbances on the cutting dynamics. However, few works consider uncontrolled periodic disturbances, whose sources are spindle units and the supporting system of the machine. These disturbances also have a significant impact on the final quality indicators of the cutting process. Therefore, an urgent task in the mechanical engineering technology is to establish patterns of the effect of uncontrolled disturbances on the dynamics of the cutting process, which is particularly important for the development of systems for the automated selection of operating conditions or vibration diagnostics systems. This research is aimed at determining the mechanism of influence of periodic fluctuations of processing parameters caused by vibration disturbances on the temperature of the front face of the turning cutter, which is the key indicator of the development of diffusion wear of the carbide tool.Materials and Methods. The study of the effect of periodic disturbances on the temperature of the front face of the tool was performed in two stages. At the first stage, based on a full-scale experiment on finishing longitudinal turning of blanks made of 10GN2MFA steel with cutters with T15K6 hard alloy plates, the parameters of the disturbance model in the system were identified, namely, the oscillatory accelerations of the tool under its wear. The vibration characteristics of the 16K20 universal lathe were measured using a vibration stand assembled on the basis of AP2089–100–3.3–02B vibration transducers, with a signal sampling frequency of 10 kHz. At the second stage, a digital study of the simulated disturbances and their effect on the dynamics of the cutting process was carried out. The results of the experiments were analyzed to compare the calculated maximum temperature of the front face of the tool at the moments when one of the specified output parameters of processing, obtained as a result of digital modeling, reaches an extreme value under the impact of periodic disturbances.Results. It has been established that fluctuations in the parameters of operating cutting modes caused by periodic disturbances lead to temperature fluctuations in the contact zone of the tool and the blank. The greatest impact on the temperature in the cutting system under study was exerted by the combination of processing parameters at the moments of reaching extreme feed values. However, when fluctuations in cutting depth and speed reached extreme values, no significant changes in contact temperature were observed.Discussion and Conclusion. The results of the conducted research emphasize the importance of analyzing the effect of periodic disturbances on pulse changes in contact temperature in the processing zone. The presented model of the relationship between tool vibrations and temperature in the cutting zone can be used to optimize turning modes. The criterion of optimality is the minimization of tool wear, which is determined on the basis of an analysis of temperature fluctuations and vibration activity signals of the tool.